Accuracy and precision of sonographic fetal weight estimation in Sweden - Linda Lindström; Sven Cnattingius; Ove Axelsson; Michaela Granfors (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Fetal growth assessment by ultrasound is an essential part of modern obstetric care. The formula by Persson and Weldner for estimated fetal weight (EFW), used in Sweden since decades, has not yet been evaluated. The objective of this study was to evaluate accuracy and precision of the formula by Persson and Weldner, and to compare it to two other formulae using biparietal diameter instead of head circumference. Material and methods The study population consisted of 31 521 singleton pregnancies delivered at 22+0 gestational weeks or later, with an ultrasound EFW performed within 2 days before delivery, registered in the Swedish Pregnancy Register between 2014 and 2021. Fetal biometric ultrasound measurements were used to calculate EFW according to the formulae by Persson and Weldner, Hadlock 2 and Shepard. Bland–Altman analysis, systematic error (mean percentage error), random error (standard deviation [SD] of mean percentage error), proportion of weight estimates within ±10% of birthweight, and proportion with underestimated and overestimated weight was calculated. Moreover, calculations were made after stratification into small, appropriate, and large for gestational age (SGA, AGA and LGA), respectively, and gestational age at examination. Results For the formula by Persson and Weldner, MPE was −2.7 (SD 8.9) and the proportion of EFW within ±10% from actual birthweight was 76.0%. MPE was largest for fetuses estimated as severe SGA (<3rd percentile, −5.4) and for the most preterm fetuses (<24 weeks, −5.4). For Hadlock 2 and Shepard's formulae, MPE were 3.9 (SD 8.9) and 3.4 (SD 9.7), respectively, and the proportions of EFW within ±10% from actual birthweight were 69.4% and 67.1%, respectively. MPE was largest for fetuses estimated as severe LGA (>97th percentile), 7.6 and 9.4, respectively. Conclusions The recommended Swedish formula by Persson and Weldner is generally accurate for fetal weight estimation. The systematic underestimation of EFW and random error is largest in extreme preterm and estimated SGA‐fetuses, which is of importance in clinical decision making. The accuracy of EFW with the formula by Persson and Weldner is as good as or better than Hadlock 2 and Shepard's formulae.